2004
DOI: 10.2320/matertrans.45.602
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube/Aluminium Composites with Uniform Dispersion

Abstract: Carbon nanotubes (CNTs) are attracting much interest as fibrous materials for reinforcing metal matrix composites due to their remarkable properties such as very high strength, elastic modulus, flexibility and high aspect ratios. However, due to the intricate entanglements of long and fine CNTs and resulting aggregation, disentanglement and uniform dispersion of CNTs in aluminium (Al) matrices have been found quite difficult. In addition, the poor wetting property of carbon for Al has been a great obstacle to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(107 citation statements)
references
References 5 publications
1
97
0
Order By: Relevance
“…Recently, Kwon et al reported on the tensile improvements realized in MWCNT-Al matrix composites fabricated by a nanoscale dispersion method providing a uniform dispersion of MWCNTs within the Al powders 12) followed by consolidation using spark plasma sintering (SPS) and a subsequent hot extrusion process. 13) In their study, formation of Al 4 C 3 at the interface, believed to favor the load transfer from the matrix to MWCNTs was attributed to the reaction between the liquid Al phase momentarily appeared during SPS and surface defects of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kwon et al reported on the tensile improvements realized in MWCNT-Al matrix composites fabricated by a nanoscale dispersion method providing a uniform dispersion of MWCNTs within the Al powders 12) followed by consolidation using spark plasma sintering (SPS) and a subsequent hot extrusion process. 13) In their study, formation of Al 4 C 3 at the interface, believed to favor the load transfer from the matrix to MWCNTs was attributed to the reaction between the liquid Al phase momentarily appeared during SPS and surface defects of MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…A precursor aimed at dispersing CNTs well was produced by the nanoscale dispersion method Noguchi et al, 2004). The precursor consisted of commercial gas atomized Al powder (ECKA Granules Co. Ltd., Japan, purity 99.85%, average particle size 14.82μm), multi-walled carbon nanotube (MWCNT, ILJIN Co. Ltd., Korea, purity 99.5%, average diameter and length 20 nm and 15 ), and natural rubber (NR).…”
Section: Methodsmentioning
confidence: 99%
“…The applications include the use of CNTs in energy storage and energy conversion devices [82]- [87], high-strength composites [88]- [94], nanoprobes and sensors [95]- [116], actuators [117]- [124], electronic devices [7], [125]- [134], production of nanorods using CNTs as reacting templates [135]- [138], catalysis [139]- [144], and hydrogen storage media [145]- [151]. However, this paper attempts to report the existing and future applications of CNTs in the biomedical industry exclusively.…”
Section: Applicationsmentioning
confidence: 99%